Gambaran Pemanfaatan Pelayanan Kesehatan Gigi dan Mulut oleh Pasien ODHA di Puskesmas Puger dan Puskesmas Jember Kidul Tahun 2019 - Rinda Puspa Safitri; Elyda Akhya Afida Misrohmasari; Hestieyonini Hadnyanawati; Kiswaluyo Kiswaluyo; Surartono Dwiatmoko (Fakultas Kedokteran Gigi Universitas Jember, 2022)
HIV-AIDS is a complex health problem and the number of cases increases year by year. The highest number of new HIV-AIDS cases in East Java in 2018 was found in Jember at Primary Health Center (PHC) of Puger and Jember Kidul. In PLWHA (People Living with HIV-AIDS) patients, HIV-AIDS gives manifestation in their oral cavity. PHC plays a role in handling oral health problems of PLWHA and also HIV-AIDS problems. Purpose was to determine the utilization of oral health services by PLWHA in primary health center of Puger and Jember Kidul in 2019. This research was a descriptive study by analyzing secondary data. The data was taken from medical record data of VCT and registration book of oral health services at PHC of Puger and Jember Kidul. In 2019, there were 47 new PLWHA patients at PHC of Puger and there were 36 new and old PLWHA patients with oral health problems at PHC of Jember Kidul. Most of the oral health problems of PLWHA are oral candidiasis. PLWHA with oral candidiasis were treated at VCT, while caries was referred to oral health services. There were no PLWHA who utilize the oral health services in oral health services room at PHC of Puger meanwhile, the research wasn't carried out at the oral health services room of Jember Kidul primary health center due to the COVID-19 pandemic. The utilization of oral health services by PLWHA in PHC of Puger and Jember Kidul was low, and more persuasive approaches were needed to motivate PLWHA.